(3OQGSI ebGQfI dCKQ GdWQjbJjf GdJOQjH GdPcj (B( Smartfootball ) (3h chQaQ (B( Corver Coching ) (3Ydi JfejI GdegGQGJ GdGSGSjI ddGYHj cQI GdbOe dCbd ef (B15 (3SfI OQGSI JLQjHjI CLQjJ Ydi fGOj GdHQGYe GdQjGVjI HGJfI dCbd ef (B15 (3SfI s - (3HQGfj , QTjO s; (3bGSej, CMSfs; (3eYgO GdJQHjI GdHOfjI h GdQjGVjI, LGeYI GdLRGFQ (B3 s ((3GdLRGFQ s, 2022)
(3gOaJ gPg GdOQGSI Edi GdJYQa Ydi ebGQfI JCKjQ cd ef GdWQjbJjf GdJOQjHjJjf MjK GbJQM GdHGMK HQfGeL JOQjHj HWQjbI chQaQ GdJOQjHjI (B(Coerver coaching) (3hHQfGeL JOQjHj HWQjbI GdJOQjH GdPcj (B(Smartfootball) (3aj JfejI GdegGQGJ GdCSGSjI ddGYHj cQI GdbOe Gbd ef (B15 (3SfI aj JeQjQ hGSJbHGd GdcQI (B(pass and receive)(3, JfWjW GdcQI(B(juggling)(3, JSOjO GdcQI (B(Shooting)(3, OMQLI GdcQI(B(Dribbling)(3, hGdJeQjQ GdWhjd (B(Driven). (3hGSJNOe GdHGMK GdefgL GdJLQjHj dedGFeJg hWHjYI GdHMK, ajeG JchfJ cd YjfI ef GdeLehYI ef (B18 (3dGYH cQI GdbOe aFI Cbd ef (B15 (3aj aQjb GdHQGYe GdQjGVjI HGJfI, WHb YdjgG GdHQfGeL GdJOQjHj GdebJQM, GdgOa ef hQGA gPg gh GbJQGM HQfGeL JOQjHj HWQjbI chQaQ GdJOQjHjI (B(Coerver coaching) (3hWQjbI GdJOQjH GdPcj (B(Smartfootball)(3, hGdcTa Yf MLe GdJCKjQ dcd WQjbI Ydi GdLGfH GdJbfj aj GdegGQGJ GdeOQhSI, hJhUd GdHGMK aj gPg GdOQGSI Gdi(B: " (3cd ef WQjbJj GdJOQjH GdeOQhSJjf GdJOQjH HWQjbI GdJOQjH GdPcj (B(Smartfootball) (3hWQjbI chQaQ GdJOQjHjI (B(Coerver coaching) (3JDKQGf EjLGHjG Ydi egGQGJ dGYHj cQI GdbOed Cbd ef (B15 (3SfI GdeTGQcjf aj GdJOQjH(B. " (3dG jhLO gfGc aQb Ph OdGdI EMUGFjI Hjf BKGQ WQjbI chQaQ GdJOQjHjI (B(Coerver coaching) (3hWQjbI GdJOQjH GdPcj (B(Smartfootball)(3Ydi GdegGQGJ GdJGdjI ddGYHj cQI GdbOe GdeTGQcjf aj GdOQGSI(B: " (3OMQLI GdcQI (B(Dribbling): " (3dJMce eY GdSQYI(B. " (3JeQjQ hGSJbHGd GdcQI (B(Pass and Receive). " (3GdJSOjO (B(Shooting). " (3gfGc aQb Ph OdGdI EMUGFjI Hjf BKGQ WQjbI chQaQ GdJOQjHjI (B(Coerver coaching) (3hWQjbI GdJOQjH GdPcj (B(Smartfootball) (3dUGdM WQjbI chQaQYdi egGQGJ(B: " (3JfWjW GdcQI ddGYHj cQI GdbOe GdeTGQcjf aj GdOQGSI MjK cGfJ GdBKGQ GdEjLGHjI dWQjbI chQaQ GdJOQjHjI (B(Coerver coaching) (3CMSf aj MGdI JfWjW GdcQI HGdQCS hHeTW GdbOe(B. " (3gfGc aQb Ph OdGdI EMUGFjI Hjf BKGQ WQjbI chQaQ GdJOQjHjI (B(Coerver coaching) (3hWQjbI GdJOQjH GdPcj (B(Smartfootball) (3dUGdM GdJOQjH GdPcj Ydi egGQI(B: " (3GdJeQjQ GdWhjd ddGYHj cQI GdbOe GdeTGQcjf aj GdOQGSI MjK cGfJ GdBKGQ GdEjLGHjI dWQjbI GdJOQjH GdPcj (B(Smartfootball) (3CMSf aj egGQI GdJeQjQ GdWhjd(B. s
(3OcJhQGIs
Keywords: (3GdJOQjH GdQjGVjs; (3GdJOQjH GdQjGVj GdfNHhjs; (3cQI GdbOes